Labor Market Dynamics, Informality and Regulations in Latin America - David, Antonio; Pienknagura, Samuel; Roldos, Jorge (Washington, D.C. : International Monetary Fund, 2020)
Labor markets in Latin America and the Caribbean (LAC) are characterized by high levels of informality and relatively rigid regulation. This paper shows that these two features are related and together make the speed of adjustment of employment to shocks slower, especially when regulations are tightly enforced. Evidence suggests that strict labor market regulations also have an adverse effect on medium-term growth. While both regulations on prices (minimum wages) and quantities (employment protection) decrease the speed of adjustment to shocks, they appear to be binding in different phases of the cycle-the former affects mostly the (net) job creation margin and the latter the (net) job destruction margin. The results also highlight possible interactions between labor market regulations and the effectiveness of macro-stabilization tools-including exchange rate depreciation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet